2011
DOI: 10.1016/j.limno.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton dynamics and cyanobacterial dominance in Murchison Bay of Lake Victoria (Uganda) in relation to environmental conditions

Abstract: a b s t r a c tMurchison Bay is a shallow embayment in the north-western part of Lake Victoria, strongly influenced by urban pollution from the Ugandan capital Kampala. Two stations, representing the semi-enclosed innermost part of the bay and the wider outer part of the bay, were sampled in the period from April 2003 to March 2004, in order to assess the phytoplankton community and the nutrient status in the bay. Murchison Bay was highly eutrophic with average concentrations (n ¼ 25) of total phosphorous 490 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 38 publications
6
52
0
1
Order By: Relevance
“…Although some studies (Berakhi, 2013;Kimwaga et al, 2012;Maitima et al, 2010;Mango et al, 2011;Masanja, 2013;Mati at al., 2005;Muhati et al, 2008;Musamba et al, 2011) have quantified land use and cover changes in some catchments of the lake, yet there are other catchments for instance, the Murchison Bay catchment of the lake situated in Uganda with little or no information about the extent of land use and land cover change. For instance, in parts of the Murchison Bay catchment of the Lake Victoria, different studies (Akurut et al, 2014;Banadda et al, 2009;Haande et al, 2011;JTR, 2015;Mbabazi et al, 2010) have reported the rising levels of pollution and its increasing impact as a result of expansion of Kampala city, wetland area transformations, poor agricultural practices and deforestation. However, the magnitude and the rate of these land use and cover changes have not been quantified in the Murchison Bay catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies (Berakhi, 2013;Kimwaga et al, 2012;Maitima et al, 2010;Mango et al, 2011;Masanja, 2013;Mati at al., 2005;Muhati et al, 2008;Musamba et al, 2011) have quantified land use and cover changes in some catchments of the lake, yet there are other catchments for instance, the Murchison Bay catchment of the lake situated in Uganda with little or no information about the extent of land use and land cover change. For instance, in parts of the Murchison Bay catchment of the Lake Victoria, different studies (Akurut et al, 2014;Banadda et al, 2009;Haande et al, 2011;JTR, 2015;Mbabazi et al, 2010) have reported the rising levels of pollution and its increasing impact as a result of expansion of Kampala city, wetland area transformations, poor agricultural practices and deforestation. However, the magnitude and the rate of these land use and cover changes have not been quantified in the Murchison Bay catchment.…”
Section: Introductionmentioning
confidence: 99%
“…It covers a total area of about 62 km 2 and can further be split into the Inner and Outer Bay; as their characteristics differ tremendously. Inner Murchison Bay (IMB) has an area of about 18.4 km 2 and an average depth of 3.2 m. The IMB has an average catchment area of 282 km 2 comprising of both wetlands and urban areas of the city with the biggest drainage inlet being the Nakivubo channel which passes through Kampala City.…”
Section: Murchison Baymentioning
confidence: 99%
“…Studies have reported persistent outbreak of algal blooms around the lake shores and increasing mass occurrences of cyanobacteria especially near inshore areas of the lake which is indicative of increased nutrient pollution (Haande et al [2] and Cózar et al [17]). Physicochemical measurements along the shores and bays of Lake Victoria were found to differ greatly and are mostly influenced by the extents of the bordering wetlands.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Another embayment of interest on Lake Victoria is the Murchison Bay, a receiver-end for industrial and municipal discharges from Kampala City, Uganda's capital (Banadda et al, 2009;Birungi et al, 2007;Haande et al, 2011). The aim of this study was to determine the concentration magnitude of PCDD/Fs and PBDEs in sediments and fish from the Murchison Bay and to compare the results with those obtained in studies elsewhere.…”
Section: Introductionmentioning
confidence: 99%